Technological characteristics of cataract surgery in eyes with posterior chamber phakic intraocular lens implanted previously - D.O. Marshava; Iu.M. Lazar (Journal of Ophthalmology, 2016)
Introduction. Implantation of phakic intraocular lenses (PIOL) is used for the correction of high myopia. The problem of PIOL implantation is that cataract may develop in a long-term period after surgery due to the contact of constructive PIOL elements to anterior and posterior chamber tissues. So, the development of advanced surgical techniques enabling to perform bilensectomy as safely and quickly as possible is of a great importance.